The Impact of Board Influence on the Role of Eco-innovation in the Company Success and Non-Success - Bekhradi Nasab, Vahid; Mehdi Afzali, Sayyed (International Journal of Business Management and Entrepreneurship, 2022)
Considering that today's competitive environment is growing and the movement of organizations towards complexity and dynamism has started, the ability to learn earlier and faster than competitors will be the only relative advantage in the next decade and should The prospects and long-term and short-term contributions of organizations should be examined in a different way, and creativity, innovation along with the use of current information should be an inseparable part of managers' decision-making, and only an organization can claim superiority and success that To use the capabilities, commitment and learning capacity of employees at all levels of the organization in the best way. Based on this, the current research has studied the Board influence on the role of environmental innovation in the success and stock price risk. The statistical population of the research is all the Companies listed in Tehran Stock Exchange to the stock exchange, the period from 2014 to 2019 and the sample is 153 companies. Based on the investigations, the findings showed that environmental innovation has a positive and significant effect on the company's long-term success, and with the Board influence in the company, the role of environmental innovation on the company's long-term success shows a better effect. Also, environmental innovation has a positive and significant effect on the company's success in the short term, and with the Board influence in the company, the role of environmental innovation on the company's short-term success becomes more colorful (intense). Finally, environmental innovation has a negative and significant effect on the Stock price risk in the long run.